Synthesis, characterization, applications, and environmental impacts of nanofluid thermosetting adhesives for sustainable bio-composites: A review - Dewi Kurnianingsih Arum Kusumahastuti; Ina Winarni; Efri Mardawati; Apri Heri Iswanto; Muhammad Adly Rahandi Lubis (Case Studies in Chemical and Environmental Engineering)
Nanofluids are created by floating small nanoparticles in base fluids, such as water or ethylene glycol, with or without stabilizing methods. The particle size in nanofluids is less than 100 nm. Nanofluid thermosetting adhesives could be developed by exploiting their excellent thermal and rheological properties, which are crucial in improving material performance and reducing the cost of materials. While developing nanofluid thermosetting adhesives offers excellent opportunities, it also requires overcoming several technical and environmental effects that should not be ignored. This paper reviewed the methods of synthesizing, characterization, applications, and the environmental impact of nanofluid thermosetting adhesives for sustainable bio-composite.